Comparison of thicknesses of the myocardial fibers of anencephalic and normal human fetuses - Öztürk, A. Hakan; Kurtoğlu, Zeliha; Tuncel, Mürvet; Uluutku, Haluk; Aktekin, Mustafa; Çamdeviren, Handan (The Turkish Journal of Pediatrics, 2002)
When heart transplantation is needed in newborns, brain death should be confirmed, and the heart should not be exposed to hypoxia. The anencephalic newborn has been presented as a donor in heart transplantation. It is important, therefore, to evaluate possible morphological differences in the hearts of anencephalic cases. In this study, muscle fibers were studied in 10 anencephalic and 10 normal fetuses (27-35 weeks) and the results were compared. Random samples were taken from the upper 1/3 of the right ventricle’s posterior wall and processed for light microscopic examination. Thicknesses of the 100 myocardial muscle fibers for each fetus were evaluated. There was statistically no significant difference between the anencephalic and normal fetus groups and the sex groups. Morphological features of the transplant probably affects the performance of the heart after operation. The anencephalic fetuses could be unique donors for heart transplantation.